Cytotoxicity Evaluation of Photosensitizer-Conjugated Hexagonal Upconverting Nanoparticles - Mykhailo Nahorniak; Viktoriia Oleksa; Taras Vasylyshyn; Ognen Pop-Georgievski; Eliška Rydvalová; Marcela Filipová; Daniel Horák (Nanomaterials, 2023)
In this report, we synthesized hexagonal NaYF4:Yb,Er upconverting nanoparticles (UCNPs) of 171 nm in size with a narrow particle size distribution. To address their colloidal stabi-lity in aqueous media and to incorporate a photosensitizer that can produce reactive singlet oxygen (1O2) to kill tumor cells, UCNPs were conjugated with 6-bromohexanoic acid-functionalized Rose Bengal (RB) and coated with PEG-alendronate (PEG-Ale). The particles were thoroughly characterized by transmission electron microscopy, dynamic light scattering, ATR FTIR, X-ray photoelectron spectroscopy, thermogravimetric analysis, and spectrofluorometry, and 1O2 formation was detected using a 9,10-diphenylanthracene spectrophotometric probe. Cytotoxicity determination on rat mesenchymal stem cells by using the MTT assay showed that neutralization of the large positive surface charge of neat UCNPs with PEG-Ale and the bound RB sensitizer significantly reduced the concentration-dependent cytotoxicity. The presented strategy shows great potential for the use of these particles as a novel agent for the photodynamic therapy of tumors.